Fenomenologi Pembentukan Karakter Santri Di Ma'had Tahfidz Al-Ansor Medan - Herman Suhdi; Muhammad Takwin Machmud; Silvia Mariah Handayani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to understand the meaning of students’ lived experiences in the process of character formation through non-formal education at Ma’had Tahfidz Al-Ansor Medan. Using a qualitative phenomenological approach, this research explores how students experience daily interactions with teachers, peers, and the pesantren environment an atmosphere rich in religious and disciplinary values. Data were collected through in-depth interviews, participatory observations, and documentation of teaching and character-building activities. The findings reveal that character formation at Ma’had Tahfidz Al-Ansor occurs through three main dimensions: exemplary modeling (uswah), habituation (ta‘wid), and the internalization of spiritual values in daily routines such as Qur’an memorization, congregational prayers, and community service activities. These dimensions collectively shape a character pattern grounded in sincerity, responsibility, and independence. From a phenomenological perspective, students perceive the pesantren’s non-formal education not merely as religious instruction but as a spiritual journey toward developing noble character (akhlaq al-karimah). The study concludes that non-formal education in pesantren plays a significant role in fostering students’ character through meaningful existential experiences.